Isolation of Oxamyl-degrading Bacteria and Identification of cehA as a Novel Oxamyl Hydrolase Gene - Rousidou, Konstantina; Chanika, Eleni; Georgiadou, Dafne; Soueref, Eftychia; Katsarou, Demetra; Kolovos, Panagiotis; Ntougias, Spyridon; Tourna, Maria; Tzortzakakis, Emmanuel A.; Karpouzas, Dimitrios G. (Frontiers in Microbiology, 2016)
Microbial degradation is the main process controlling the environmental dissipation of the nematicide oxamyl. Despite that, little is known regarding the microorganisms involved in its biotransformation. We report the isolation of four oxamyl-degrading bacterial strains from an agricultural soil exhibiting enhanced biodegradation of oxamyl. Multilocus sequence analysis (MLSA) assigned the isolated bacteria to different subgroups of the genus Pseudomonas. The isolated bacteria hydrolyzed oxamyl to oxamyl oxime, which was not further transformed, and utilized methylamine as a C and N source. This was further supported by the detection of methylamine dehydrogenase in three of the four isolates. All oxamyl-degrading strains carried a gene highly homologous to a carbamate-hydrolase gene cehA previously identified in carbaryl- and carbofuran-degrading strains. Transcription analysis verified its direct involvement in the hydrolysis of oxamyl. Selected isolates exhibited relaxed degrading specificity and transformed all carbamates tested including the oximino carbamates aldicarb and methomyl (structurally related to oxamyl) and the aryl-methyl carbamates carbofuran and carbaryl which share with oxamyl only the carbamate moiety